El poder de los cautivos: relaciones sociales entre abipones e hispanocriollos en las fronteras del Chaco austral (siglo XVIII) - Carina P. Lucaioli (Centre de Recherches sur les Mondes Américains, 2011)
This paper deals with the problem of captives among the Abipones groups of Chaco during the 18th century. For the above-mentioned groups the practice of captive-taking was complex because it involved political, social, economic and symbolic aspects. Captives themselves came to be key elements for the development of colonial interethnic relations since they promote the interaction with others in many ways. The multiple meanings and functions they concentrated were strategically manipulated by the Abipones to organize the frontier relations on their behalf. Our task will be to identify the captives’ functions and to draw the complex net of social relations establish around them.